EFEKTIVITAS PERMAINAN HALANG RINTANG DALAM MENINGKATKAN KEMAMPUAN MOTORIK KASAR GANGGUAN SPEKTRUM AUTISME - Taftazani , Maulfi Afiffati; Kurniawan, Hendri (Tahta Media Group, 2024)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder which is also characterized by gross motor delays which affect the development of functional abilities. Obstacle games provide sensory input that allows children to coordinate their body parts well. This study aims to determine the effectiveness of obstacle games on gross motor skills in ASD children aged 3-10 years. Method: Quantitative research using a pre-experiment one group pretest-posttest design. The research sample of 20 people was obtained using a purposive sampling technique. Motor ability variables were measured using the Test of Gross Motor Development-2 (TGMD-2) instrument. Data analysis used a paired t-test and n-gain score test with SPSS 25 software. Results: The majority of the research samples were male (85%), pre-school age (85%), and were at the average GARS category level (75%). Hypothesis testing showed a p-value = 0.000 (p<0.05) which means there is a significant difference in gross motor skills in children with ASD between before and after the obstacle course game. The N-Gain Score test obtained a value of 0.42, which means it is effective in the medium category. Conclusion: The obstacle course game is effective in improving the gross motor skills of children with autism spectrum disorders.